A perspectiva da construção do letramento literário na leitura de contos de fadas e recontos para o fundamental I - Dias, Thamyres de Oliveira (2023)
This research belongs to the de Professional Master in Letras (PROFLETRAS-UFU), which encourages educators to reflect on everyday practices, through this proposition, the objective was to carry out a reflection about the approaches to literary reading in the classroom, Aimimg to contribute in the formation of young readers and the encouragement children’s literature. In order to teach In grades begins the literacy process, such study is intended begginers students of Elementary school, In municipal public school In Goiás state.The choosen genres were fairy tales and their respectives tales , Inside of the perspective multiliteracies, in which the Classic tale little Red hiding hood and the book colored little hood by de José Roberto Torero e Marcus Aurelius Pimenta, contribute to awakening to fantastic universe.In the elaboration of didatical proposal, the methodology usei was action search of Thiollent (1986) the beginning used a logbook written by researcher to continuous registry in order to pereceive challenges main of reading practices. Based on the theories of the authors: Soares (2001, 2014, 2015, 2021), to conceptualize literacy. To conceptualize and understand literary literacy, the reference is the work of Cosson (2006), through the Basic Sequence, emphasizing the short story lilac little hood, contained in the chosen work.Corso e Corso (2006), Rojo (2012) and Tatar ( 2004). About the methodological support, the research is based on the guidelines of the BNCC (2018) and on the contributions of Rodari (1982) and Thiollent (1986). The didactic proposal includes systematized workshops, with stages of a literary literacy work, which were made available in the final product in the form of an activity notebook.